Ikaw ang mahal ko - Viva Films (Viva Films], 2006)
Fernando Poe, Jr. is Pilo, a mild-mannered bodyguard who's only daughter considers every single woman she knows is a prospective new mother. Vilma Santos, is Miling, an old fashioned probinsyana who stows away when she learns that her aunt has betrothed her to the richest man in town. They meet in the most bungling of situations and they become, uhh, fast enemies. But when two, people are meant to stay together, it doesn't really matter if their first meeting turns disastrous.